Inquiries and Problem Based Learning (Pbl) Assistant Multimedia Learning Models in Improving Students' Critical Thinking Skills - Idah Paridah; Prasetyorini Prasetyorini; Dadang Jaenudin (Universitas Pakuan, 2021)
This study aims to determine the interaction between the multimedia-assisted inquiry learning model and the multimedia-assisted Problem Based Learning (PBL) model on critical thinking skills and to determine the differences in critical thinking skills between students using inquiry learning and PBL. This study used a quasi-experimental with static group pre-posttest design. The implementation of the learning involved students of class XI IPA who were studying the reproductive system, respectively 37 students for the inquiry class and 33 students for the PBL class. The instrument used was an essay question consisting of 10 questions, and a questionnaire to collect student and teacher responses. The results showed that the inquiry learning model and PBL were able to improve students' critical thinking skills, and overall, the PBL model is better than the inquiry learning model. Students and teachers gave a positive response to the inquiry learning model and PBL.